Magnetic and Plasmonic Composite Nanostructures for Creating Optical Filters at Substance and Material Diagnostics Systems - R. S. Smerdov; Yu. M. Spivak; V. A. Moshnikov; A. S. Mustafaev (Известия высших учебных заведений России: Радиоэлектроника, 2021)
Introduction. Porous silicon (PS) and materials on its basis are of interest for application in nanoelectronics, targeted drug delivery and advanced gas sensors. In addition, PS-based nanostructures are promising as filters in fibre-optic communication systems, since conventional thin-film deposition filters possess sidebands in their operating range thus requiring high vacuum for nanometer-thick coatings.Aim. To develop optical band-stop filter prototypes based on composite magnetic nanoparticles and the effect of localized surface plasmon resonance (LSPR) in an array of silver nanoparticles located on the PS surface. Materials and methods. The development and synthesis of nanostructures for the creation of filter prototypes. The double differentiation method in conjunction with Mie absorption theory was used for processing and analyzing the prototypes attenuation characteristics.Results. Two prototypes were developed. An analysis of the attenuation characteristics of a prototype based on SiO2 matrix functionalized by FemOn indicated that the parameters of the detected absorption bands depend on the size of FemOn nanoparticles. The attenuation characteristics of the LSPR-based prototype contain two absorption bands. The center wavelength value in the band caused by LSPR in the array of silver nanoparticles, close to spherical, is 367.5 nm. Excitation of LSPR in silver quantum clusters, manifested by the appearance of the corresponding band, occurs at a wavelength of 265.5 nm. The suppression in each of the bands can be controlled by changing the parameters of the PS matrix synthesis.Conclusion. Despite the disadvantages, e.g. a relatively low accuracy in setting the center wavelength, as well as certain difficulties concerned with reducing the unevenness in the absorption band, the obtained prototypes surpass existing analogues and are prospective for the development of compact analysis and diagnostics systems in a wide energy range.